Bacterial isolates from bryozoan Pleurocodonellina sp.: Diversity and antimicrobial potential against pathogenic bacteria - Meezan Ardhanu Asagabaldan; Gilles Bedoux; Nathalie Bourgougnon; Rhesi Kristiana; Diah Ayuningrum; Agus Sabdono; Agus Trianto; Ocky Karna Radjasa (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Asagabaldan MA, Bedoux G, Bourgougnon N, Kristiana R, Ayuningrum D, Sabdono A, Trianto A, Radjasa OK. 2019. Bacterial isolates from bryozoan Pleurocodonellina sp.: Diversity and antimicrobial potential against pathogenic bacteria. Biodiversitas 20: 2528-2535.  There is an urgent need to discover new compounds with antibacterial activity, which can be developed into lead structures for the treatment of human disease caused by multidrug-resistant (MDR) bacteria. In this study, we focussed on bryozoan-associated bacteria to screen them toward antibacterial activities, since the microbiome of these organisms can still be regarded as under-investigated. Most of the few publications about bryozoan-associated bacteria focused on taxonomy and the potential as producers of antibacterial natural products were neglected. Four specimens of bryozoan Pleurocodonellina sp. were collected from Teluk Awur, Jepara in Java Sea, Indonesia. Therefrom, 56 bacterial strains were isolated, and 17 displayed antibacterial activities against MDR bacteria Pseudomonas aruginosa, Klebsiella pneumoniae, Acinetobacter baumannii, Enterobacter cloacae, and methicillin-resistant Staphylococcus aureus (MRSA). Taxonomic identification of the bacteria by 16S rRNA gene sequencing revealed them belonging to the genera Virgibacillus, Pseudoalteromonas, Halomonas, and Bacillus. Most interestingly, the genus Virgibacillus was dominantly obtained from the Pleurocodonellina sp. specimens, i.e., 12 active isolates. Nevertheless, the best activities against MDR bacteria (both Gram-positive and Gram-negative) were contributed to isolates showing >99% identity to Pseudoalteromonas. The results further suggest adding the genus Virgibacillus as bacteria associated with bryozoan, since to the best of our knowledge there were no reports of this genus isolated from bryozoan.